The Effect of Relationship Marketing and Promotion on Consumer Loyalty through Consumer Satisfaction Study on Shopee Users in Sumenep District - Moh Rizal (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2022)
With the development in information technology that is increasingly modern, the world of trade and business is also growing. This is a challenge for shopee to be able to continue to bring new innovations and maintain consumer loyalty. Therefore, considering the importance of providing convenience and security to buyers and sellers, it also provides promotions that can attract consumers to make purchases for buyers. Building strong and mutually beneficial relationships so that in the concept of relationship marketing, marketers strongly emphasize the importance of long-term good relationships with consumers. This research aims to determine the partial influence and mediation between relationship marketing and promotion on consumer satisfaction and consumer loyalty. The study used a non-probability sampling method with the spread of questionnaires online by 110 respondents. And research analysis techniques use Partial Least Square (PLS) with program 3.0. The results showed partially relationship marketing and promotion had a positive and significant effect on consumer satisfaction, relationship marketing and consumer satisfaction had a positive and significant effect on consumer loyalty. Promotions have a positive but insignificant effect on consumer loyalty. Consumer satisfaction is able to mediate between the influence of relationship marketing on consumer loyalty, while consumer satisfaction has not been able to mediate between the influence of promotion on consumer loyalty.Keywords: relationship marketing, promotion, consumer satisfaction, consumer loyalty